Solid electrolyte and all-solid-state battery comprising same
By doping specific cations into solid electrolytes with sulfur-silver germanium ore-type crystal structure, the problem of sulfide-based solid electrolyte reacting with air under low humidity conditions is solved, and excellent air stability and high ionic conductivity are achieved.
Patent Information
- Application Number
- CN202380059120.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-11
AI Technical Summary
The sulfide-based solid electrolyte reacts with moisture in the air under low humidity conditions, producing harmful gas hydrogen sulfide, affecting workers' safety and reducing the performance of the electrolyte.
A solid electrolyte with a sulfur-silver germanium ore-type crystal structure doped with specific cations is used. The ratio of the ion radius of the cation to the S2-ion radius is between 0.20 and 0.30, which improves the air stability of the electrolyte.
By doping cations, the moisture stability of the solid electrolyte is significantly improved, the production of hydrogen sulfide is suppressed, and the high ionic conductivity is maintained, and the chemical resistance of the battery is improved.
Smart Images

Figure CN119605013A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to Korean Patent Application No. 10-2022-0106849, filed on August 25, 2022, the disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to a solid electrolyte having an argyrodite-type crystal structure with improved air stability and an all-solid-state battery comprising the same. Background Art
[0004] All-solid batteries are batteries that replace the liquid electrolyte filled between the positive and negative electrodes of conventional lithium secondary batteries with solid batteries. Among them, because its energy density is higher than that of conventional batteries, and it is safe because there is no risk of explosion, it has attracted much attention as the next generation of batteries. The solid electrolyte used in all-solid batteries is a solid material that can conduct lithium ions in the battery, where it has a high ionic conductivity comparable to the ionic conductivity of the electrolyte currently used in lithium secondary batteries. The core materials that constitute the solid electrolyte include polymers, sulfides or oxides, and among them, sulfide-based solid electrolytes with high ductility and ionic conductivity are evaluated as suitable for preparing large-scale batteries with high capacity.
[0005] However, since the sulfide-based solid electrolyte is highly reactive to moisture, there is a problem in that it reacts not only with moisture in the air but also with moisture under low humidity conditions to produce harmful gas hydrogen sulfide (H2S). Therefore, the toxic hydrogen sulfide may not only adversely affect the safety of workers but also degrade the performance of the sulfide-based solid electrolyte itself.
[0006] Therefore, there is a need to develop a sulfide-based solid electrolyte having excellent air stability. Summary of the invention
[0007] Technical issues
[0008] It is an object of the present invention to provide a solid electrolyte with improved air stability, in particular moisture stability.
[0009] However, the objects of the present invention are not limited to the above objects, and other objects not described herein will be clearly understood by those skilled in the art from the following description.
[0010] Technical Solution
[0011] In order to solve the above problems, the present invention provides a solid electrolyte and an all-solid-state battery.
[0012] (1) The present invention provides a solid electrolyte having an argyrodite-type crystal structure doped with cations, wherein the cations have an ionic radius (r) (unit: Å) value of 0.20 to 0.30 for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ).
[0013] (2) The present invention provides the solid electrolyte described in (1) above, wherein the cation has a ratio (c / r) of the ion oxidation number (c) value to the ion radius (r) (unit: Å) value of 7.00 to 14.00.
[0014] (3) The present invention provides the solid electrolyte described in (1) or (2) above, wherein the solid electrolyte has a composition represented by Chemical Formula 1.
[0015] [Chemical formula 1]
[0016] Li a (P 1-b M b )S c X d
[0017] In Chemical Formula 1,
[0018] M is at least one selected from tin (Sn), niobium (Nb), nickel (Ni), germanium (Ge), gallium (Ga), and aluminum (Al),
[0019] X is at least one selected from fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and
[0020] 5.0<a<7.5, 0<b≤0.7, 3.5≤c≤7 and 0.8≤d≤1.7.
[0021] (4) The present invention provides the solid electrolyte described in any one of (1) to (3) above, wherein M is at least one selected from Sn, Nb, Ge and Al.
[0022] (5) The present invention provides the solid electrolyte described in any one of (1) to (4) above, wherein the ratio of the number of moles of M to the sum of the number of moles of P (x) and the number of moles of M (y) (y / (x+y)) satisfies 0.01 to 0.7.
[0023] (6) The present invention provides the solid electrolyte described in any one of (1) to (5) above, wherein the ion conductivity retention rate according to Formula 1 is 55% or more.
[0024]
[0025] In formula 1,
[0026] The initial ionic conductivity is a value measured at 22° C. immediately after preparing the solid electrolyte, and
[0027] The ionic conductivity after moisture exposure is a value measured at 22° C. immediately after the solid electrolyte is exposed to air having a relative humidity of 1.91% for 5 hours.
[0028] (7) The present invention provides the solid electrolyte described in (6) above, wherein the initial ion conductivity is in the range of 2.0 mS / cm to 20.0 mS / cm.
[0029] (8) The present invention provides the solid electrolyte described in any one of (6) or (7) above, wherein the ion conductivity after exposure to moisture is in the range of 1.4 mS / cm to 18.0 mS / cm.
[0030] (9) The present invention provides the solid electrolyte described in any one of (1) to (8) above, wherein the solid electrolyte has a near infrared (NIR) spectrum at 5,200 cm -1 Up to 4,725cm -1 The impurity peak is within the range, and the area increase rate of the impurity peak according to Formula 2 is in the range of 50% to 400%.
[0031]
[0032] In formula 2,
[0033] The integrated value of the impurity peak before moisture exposure is a value obtained from the NIR spectrum measured at room temperature immediately after preparing the solid electrolyte, and
[0034] The integrated value of the impurity peak after moisture exposure is a value obtained from the NIR spectrum measured at room temperature immediately after the solid electrolyte was exposed to air having a relative humidity of 1.91% for 5 hours.
[0035] (10) The present invention provides the solid electrolyte described in (9) above, wherein the integrated value of the impurity peak after exposure to moisture is in the range of 1 to 20.
[0036] (11) The present invention provides a solid electrolyte as described in any one of (1) to (10) above, wherein the average particle size (D 50 ) is in the range of 0.5μm to 4μm.
[0037] (12) The present invention provides a solid electrolyte as described in any one of (1) to (11) above, wherein the span value ([D 90 -D 10 ] / D 50 ) is less than 4.
[0038] (13) The present invention provides an all-solid-state battery comprising the solid electrolyte described in any one of (1) to (12) above.
[0039] Beneficial Effects
[0040] Since the solid electrolyte having an argyrodite-type crystal structure according to the present invention is doped with cations, the cations have an ionic radius (r) (unit: Å) value of 0.20 to 0.30 for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ), so the solid electrolyte itself has the advantage of excellent air stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a view showing X-ray diffraction (XRD) patterns of the solid electrolytes of Examples 1, 4, and 5.
[0042] Figure 2 is a view showing XRD patterns of the solid electrolytes of Comparative Examples 3, 4, and 5. DETAILED DESCRIPTION
[0043] Hereinafter, the present invention will be described in more detail to make the present invention more clearly understood.
[0044] It should be understood that the words or terms used in this specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that these words or terms should be interpreted as having meanings consistent with their meanings in the context of the prior art and the technical ideas of the present invention, based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the present invention.
[0045] The terms used herein are only for the purpose of describing specific exemplary embodiments and are not intended to limit the present invention. In the present specification, unless otherwise specified, a term in the singular form may include a plural form.
[0046] It should be further understood that when used in this specification, the terms "comprises", "includes" or "has" clarify the existence of the described features, numbers, steps, elements or their combinations, but do not exclude the existence or addition of one or more other features, numbers, steps, elements or their combinations.
[0047] In this specification, the ionic radius is the Shannon ionic radius.
[0048] In this manual, "D n " represents the particle size at n% of the volume cumulative distribution of particle sizes. That is, D 50 is the particle size at which 50% of the volume cumulative distribution of particle sizes is located, D 90 is the particle size at which the volume cumulative distribution of particle sizes is 90%, D 10 It is the particle size at which the volume cumulative distribution of particle sizes reaches 10%. n It can be measured by using a laser diffraction method. Specifically, after dispersing the measurement target powder in a dispersion medium (xylene), the dispersion medium is introduced into a commercially available particle size analyzer (e.g., Malvern Panalytical, Mastersizer 3000), and the particle size distribution is calculated by measuring the difference in diffraction patterns caused by the particle size when the particles pass through the laser beam. 10 , D 50 and D 90 It can be measured by calculating the particle diameters at 10%, 50%, and 90% of the volume cumulative distribution according to the particle diameters using a measuring instrument.
[0049] Solid electrolyte
[0050] The solid electrolyte according to the present invention has an argyrodite type crystal structure doped with cations, wherein the cations have an ionic radius (r) (unit: Å) value of 0.20 to 0.30 for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ).
[0051] The present inventors have found that, for the solid electrolyte having an argyrodite-type crystal structure according to the present invention, since it is doped with cations, the cations have an ionic radius (r) (unit: Å) value of 0.20 to 0.30 for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ), so the solid electrolyte itself not only has excellent air stability but also improves chemical resistance in dry and wet processes when preparing a battery, thereby completing the present invention.
[0052] Regarding Li6PS5Cl or Li6PS5Br used as solid electrolytes having an argyrodite-type crystal structure in the art, there is a problem in that the S contained in the solid electrolyte2- The ions react with moisture in the air and are easily decomposed. However, since the solid electrolyte having a argyrodite crystal structure according to the present invention is doped with S 2- The ion has a strong binding force, specifically, the cation has an ionic radius (r) (unit: Å) value of 0.20 to 0.30 for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ), so it can suppress the decomposition and degradation of the solid electrolyte particles when exposed to moisture or oxygen. As a result, the generation of hydrogen sulfide as a toxic gas can be suppressed, and the reduction of the ionic conductivity of the solid electrolyte can be prevented. The ionic radius (r) (unit: Å) value of the cation is 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ) can specifically be greater than 0.20, greater than 0.21 or greater than 0.25, and can be less than 0.30.
[0053] The ionic radius (r) (unit: Å) of the cations described herein is 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ) is less than 0.20, the problem is that due to the interaction between the cation and S 2- The binding force between them is low and the decomposition reaction caused by water is easy to occur. In addition, the ionic radius (r) (unit: Å) of the cations in the present invention is not very important for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ) is greater than 0.30, since the size of the cations is too large, it is difficult to dope the cations into the argyrodite-type crystal structure. Therefore, not only is there no effect of improving the moisture stability, but there is also the problem of generating impurities and reducing the ionic conductivity.
[0054] According to the present invention, the cation may have a ratio (c / r) of an ion oxidation number (c) value to an ion radius (r) (unit: Å) value of 7.00 to 14.00. In this case, since the cation can be easily doped between the cation and S 2- The P site of the binding can improve the initial ionic conductivity, and because the cations bind to S 2- Good bonding between the two can improve moisture stability.
[0055] According to the present invention, the solid electrolyte may have a composition represented by the following Chemical Formula 1. In this case, the solid electrolyte may have high ion conductivity and may have low reactivity with a lithium negative electrode, and may suppress decomposition and degradation of the solid electrolyte particles when exposed to moisture or oxygen.
[0056] [Chemical formula 1]
[0057] Li a (P 1-b M b )S c X d
[0058] In Chemical Formula 1,
[0059] M is at least one selected from tin (Sn), niobium (Nb), nickel (Ni), germanium (Ge), gallium (Ga), and aluminum (Al),
[0060] X is at least one selected from fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and
[0061] 5.0<a<7.5, 0<b≤0.7, 3.5≤c≤7 and 0.8≤d≤1.7.
[0062] According to the present invention, M is a doping element doped into a solid electrolyte having an argyrodite-type crystal structure, wherein M may be at least one selected from Sn, Nb, Ni, Ge, Ga and Al, specifically at least one selected from Sn, Nb, Ge and Al.
[0063] According to the present invention, the ratio of the mole number of M of the solid electrolyte to the sum of the mole number of P (x) and the mole number of M (y) (y / (x+y)) satisfies 0.01 to 0.7, specifically 0.01 or more, and 0.5 or less, 0.6 or less, or 0.7 or less. In this case, since the doping amount is appropriate, the solid electrolyte can exist in an argyrodite phase with no impurities or a low impurity content, and accordingly, the ionic conductivity can be improved.
[0064] According to the present invention, the ion conductivity retention rate of the solid electrolyte according to the following formula 1 may be 55% or more, specifically 55% or more, and 70% or less, 75% or less, 80% or less, 85% or less, or 90% or less.
[0065]
[0066] In formula 1,
[0067] The initial ionic conductivity is a value measured at 22° C. immediately after preparing the solid electrolyte, and
[0068] The ionic conductivity after moisture exposure is a value measured at 22° C. immediately after the solid electrolyte is exposed to air having a relative humidity of 1.91% for 5 hours.
[0069] According to the present invention, the initial ion conductivity of the solid electrolyte may be 2.0 mS / cm to 20.0 mS / cm, specifically 2.0 mS / cm or more or 2.5 mS / cm or more, and 10.0 mS / cm or less, 15.0 mS / cm or less or 20.0 mS / cm or less. The higher the ion conductivity of the electrolyte, the better, but in the case where the initial ion conductivity satisfies the above range, the effect of improving moisture stability may be excellent.
[0070] According to the present invention, the ionic conductivity of the solid electrolyte after moisture exposure may be 1.4 mS / cm to 18.0 mS / cm, specifically 1.4 mS / cm or more or 1.5 mS / cm or more, and 9.0 mS / cm or less, 10.0 mS / cm or less, 11.0 mS / cm or less, 12.0 mS / cm or less, 13.0 mS / cm or less, 14.0 mS / cm or less, 15.0 mS / cm or less, 16.0 mS / cm or less, 17.0 mS / cm or less, or 18.0 mS / cm or less. In this case, there is an advantage in that the electrolyte structure is maintained even when exposed to moisture during the battery preparation process.
[0071] According to the present invention, regarding the solid electrolyte present at 5,200 cm in the near infrared (NIR) spectrum, -1 Up to 4,725cm -1 The impurity peak within the range, the area increase rate of the impurity peak of the solid electrolyte according to the following formula 2 can be 50% to 400%, specifically more than 50%, more than 100%, more than 150% or more than 200%, and less than 350% or less than 400%.
[0072]
[0073] In formula 2,
[0074] The integrated value of the impurity peak before moisture exposure is a value obtained from the NIR spectrum measured at room temperature immediately after preparing the solid electrolyte, and
[0075] The integrated value of the impurity peak after moisture exposure is a value obtained from the NIR spectrum measured at room temperature immediately after the solid electrolyte was exposed to air having a relative humidity of 1.91% for 5 hours.
[0076] According to the present invention, the integral value of the impurity peak after the moisture exposure of the solid electrolyte may be 1.00 to 10.0, specifically 1.00 or more, and 5.00 or less or 10.0 or less. In this case, since the electrolyte structure is maintained even after moisture exposure, the ion conductivity performance can be maintained.
[0077] According to the present invention, the average particle size (D 50 ) can be 0.5 μm to 4.0 μm, specifically 0.5 μm, 1.0 μm or 2.0 μm or more, and 3.5 μm or 4.0 μm or less. In the case where the average particle size of the solid electrolyte is within the above range, the battery life characteristics can be excellent due to good contact with the electrode active material.
[0078] According to the present invention, the span value ([D 90 -D 10 ] / D 50 ) may be 4.0 or less, specifically 1.0 to 4.0. In the case where the span value of the solid electrolyte is within the above range, since the particle size is uniform, there is an advantage in that a uniform composite electrode can be prepared.
[0079] The solid electrolyte according to the present invention can be synthesized, for example, by mechanical grinding and solid phase synthesis. Specifically, according to stoichiometric weighing: at least one selected from LiCl, LiBr and LiI, Li2S, P2S5, and raw materials containing doping elements (such as SnS2, GeS2, etc.), and then mixed by ball milling. The mixed precursor thus obtained is crystallized by heat treatment and then ground again by ball milling. The mixing, heat treatment and grinding steps are carried out in an inert gas atmosphere.
[0080] All-solid-state battery
[0081] The present invention provides an all-solid-state battery comprising the solid electrolyte.
[0082] Specifically, the all-solid battery includes: a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and a solid electrolyte layer provided between the positive electrode and the negative electrode, the solid electrolyte layer including the solid electrolyte according to the present invention.
[0083] Since the all-solid battery according to the present invention has a small decrease in ion conductivity due to moisture, the initial efficiency, life characteristics, and output characteristics of the battery may be excellent.
[0084] In this case, the all-solid battery of the present invention can be prepared according to a typical method known in the art. For example, the all-solid battery of the present invention can be prepared by stacking and pressing so that a solid electrolyte layer exists between the positive electrode and the negative electrode.
[0085] (1) Positive electrode
[0086] The positive electrode may be prepared by coating a positive electrode current collector with a positive electrode slurry including a positive electrode active material, a binder, a conductive material, and a solvent.
[0087] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel whose surface is treated with one of carbon, nickel, titanium, silver, etc. can be used. Moreover, fine concavoconvexity can be formed on the surface of the positive electrode current collector to improve the bonding strength with the positive electrode active material, and the positive electrode current collector can be used in various shapes such as film, sheet, foil, net, porous body, foam body, non-woven fabric body, etc.
[0088] The positive electrode active material is a compound capable of reversibly inserting and deinserting lithium, wherein the positive electrode active material may specifically include a lithium metal oxide, wherein the lithium metal oxide includes lithium and at least one metal such as cobalt, manganese, nickel or aluminum. More specifically, the lithium metal oxide may include a lithium manganese oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium cobalt oxide (e.g., LiCoO2, etc.), a lithium nickel oxide (e.g., LiNiO2, etc.), a lithium nickel manganese oxide (e.g., LiNi 1- Y Mn Y O2 (where 0<Y<1), LiMn 2-Z Ni Z O4 (where 0<Z<2), etc.), lithium nickel cobalt oxides (e.g., LiNi 1- Y1 Co Y1 O2 (where 0<Y1<1), etc.), lithium manganese cobalt oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0<Y2<1), LiMn 2-Z1 Co Z1 O4 (where 0<Z1<2), etc.), lithium nickel manganese cobalt oxides (e.g., Li(Ni p Co q Mn r1 )O2 (where 0<p<1, 0<q<1, 0<r1<1 and p+q+r1=1) or Li(Ni p1 Co q1 Mnr2 )O4 (where 0<p1<2, 0<q1<2, 0<r2<2 and p1+q1+r2=2), etc.), or lithium nickel cobalt transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O2 (wherein M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg) and molybdenum (Mo); and p2, q2, r3 and S2 are the atomic fractions of each independent element, wherein 0<p2<1, 0<q2<1, 0<r3<1, 0<S2<1 and p2+q2+r3+S2=1), etc.), and may contain any one of them or a mixture of two or more thereof.
[0089] Among these materials, the lithium metal oxide may be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2、Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.) or lithium nickel cobalt aluminum oxide (e.g., LiNi 0.8 Co 0.15 Al 0.05 O2, etc.), and considering the significant improvement effect caused by the control of the types and content ratios of the components constituting the lithium composite metal oxide, the lithium composite metal oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, and any one of them or a mixture of two or more thereof may be used.
[0090] The content of the positive electrode active material may be 60 wt % to 99 wt %, preferably 70 wt % to 99 wt %, and more preferably 80 wt % to 98 wt %, based on the total weight of solids excluding the solvent in the positive electrode slurry.
[0091] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber, fluororubber or various copolymers thereof.
[0092] The content of the binder may generally be 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the positive electrode slurry.
[0093] The conductive material is a component for further improving the conductivity of the positive electrode active material.
[0094] The conductive material is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, conductive materials such as graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives can be used.
[0095] The content of the conductive material may generally be 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the positive electrode slurry.
[0096] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a desired viscosity is obtained when the positive electrode active material and the optional binder and the conductive material are included. For example, the content of the solvent may be such that the concentration of the solids containing the positive electrode active material and the optional binder and the conductive material is in the range of 50% to 95% by weight, preferably 70% to 95% by weight, and more preferably 70% to 90% by weight.
[0097] (2) Negative electrode
[0098] The negative electrode may be prepared, for example, by coating a negative electrode slurry including a negative electrode active material, a binder, a conductive material, and a solvent on a negative electrode collector, or a graphite electrode formed of carbon (C) or metal itself may be used as the negative electrode.
[0099] For example, in the case where the negative electrode is prepared by coating the negative electrode slurry on the negative electrode collector, the thickness of the negative electrode collector is generally 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel whose surface is treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. Moreover, similar to the positive electrode collector, the negative electrode collector may have fine surface irregularities to improve the bonding strength with the negative electrode active material, and the negative electrode collector may be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0100] The negative electrode active material may include at least one negative electrode active material selected from the group consisting of natural graphite, artificial graphite, carbonaceous materials; lithium-containing titanium composite oxide (LTO), silicon (Si), SiO x , metal (Me) such as Sn, lithium (Li), zinc (Zn), magnesium (Mg), cadmium (Cd), cerium (Ce), Ni or Fe; alloy composed of metal (Me); oxide (MeO x ); and a composite material of metal (Me) and carbon. As the negative electrode active material, specifically, a material containing silicon (Si), silicon oxide (SiO x ) or silicon-based negative electrode active materials of silicon alloys. In this case, since a thin and stable SEI layer containing siloxane bonds is formed, the high temperature stability and life characteristics of the battery can be further improved.
[0101] The negative electrode active material may be contained in an amount of 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt %, based on the total weight of solids excluding the solvent in the negative electrode slurry.
[0102] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber, fluororubber and various copolymers thereof.
[0103] The content of the binder may generally be 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode slurry.
[0104] The conductive material is a component for further improving the conductivity of the negative electrode active material. The conductive material is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, conductive materials such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.
[0105] The conductive material may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the negative electrode slurry.
[0106] The solvent may include water or an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount such that a desired viscosity is obtained when the negative electrode active material and the optional binder and the conductive material are included. For example, the content of the solvent may be such that the concentration of the solids containing the negative electrode active material and the optional binder and the conductive material is in the range of 50% by weight to 95% by weight, preferably 70% by weight to 90% by weight.
[0107] In the case where a metal itself is used as the negative electrode, the negative electrode may be a metal film itself, or may be prepared by a method in which the metal is physically bonded, rolled or deposited on the negative electrode current collector. As a deposition method, an electrodeposition method or a chemical vapor deposition method for the metal may be used.
[0108] For example, the metal film itself or the metal to be bonded / rolled / deposited on the negative electrode current collector may contain one type of metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In) or an alloy of two types of metals.
[0109] (3) Solid electrolyte layer
[0110] The solid electrolyte layer may further include a binder in addition to the solid electrolyte according to the present invention.
[0111] The binder is a component that facilitates the bonding between the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, EPDM, sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers thereof.
[0112] The content of the binder may be generally 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of the solid electrolyte layer.
[0113] The present invention provides a battery module including an all-solid battery as a unit cell, and can provide a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate performance and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0114] Preferred Implementation
[0115] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are only provided to illustrate the present invention, and various modifications and changes are possible within the scope and technical spirit of the present invention. These modifications and changes fall within the scope of the claims included herein.
[0116] Examples and Comparative Examples
[0117] Example 1
[0118] Four types of precursors Li2S, P2S5, LiBr and SnS2 were dry mixed (ball milled) at a molar ratio of 5.05:0.95:2:0.1. During the dry mixing, a planetary ball mill into which zirconia balls were introduced was used and rotated at a speed of 300 to 700 rpm for uniform mixing. Thereafter, the mixed precursor thus obtained was crystallized by heat treatment at 500 to 600° C. for 12 hours, and then again ball milled to prepare a Li2S-type crystal structure having a Li2S-type crystal structure. 6.05 P 0.95 Sn 0.05 All the above steps were carried out in an inert argon (Ar) atmosphere.
[0119] Example 2
[0120] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 6.02 P 0.98 Sn 0.02 S5Br represents the composition).
[0121] Example 3
[0122] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 6.01 P 0.99 Sn 0.01 The composition is represented by S5Br).
[0123] Example 4
[0124] A solid electrolyte (having an argyrodite-type crystal structure and having a LiI-based electrolyte) was prepared in the same manner as in Example 1, except that the four types of precursors Li2S, P2S5, LiI, and GeS2 were mixed in a molar ratio of 5.6:0.4:2:1.2. 6.6 P 0.4 Ge 0.6 S5I represents the composition).
[0125] Example 5
[0126] A solid electrolyte (having an argyrodite-type crystal structure and having a Li2S-type catalyst) was prepared in the same manner as in Example 1, except that the four types of precursors Li2S, P2S5, LiBr, and Ga2S3 were mixed in a molar ratio of 2.25:0.45:1:0.05. 5.5 P 0.9 Ga 0.1 S 4.65 Br).
[0127] Comparative Example 1
[0128] The three types of precursors Li2S, P2S5 and LiBr were dry mixed (ball milled) at a molar ratio of 5:1:2. During the dry mixing, a planetary ball mill into which zirconia balls were introduced was used and rotated at a speed of 300 to 700 rpm for uniform mixing. Thereafter, the mixed precursor thus obtained was crystallized by heat treatment at 500 to 600°C for 12 hours, and then ground again by ball milling to prepare Li6PS5Br having an argyrodite-type crystal structure. All of the above processes were carried out in an inert Ar atmosphere.
[0129] Li6PS5Br having an argyrodite-type crystal structure was used as the solid electrolyte of Comparative Example 1.
[0130] Comparative Example 2
[0131] A solid electrolyte (having an argyrodite type crystal structure and having a composition represented by Li6PS5Cl) was prepared in the same manner as in Example 1, except that three types of precursors Li2S, P2S5 and LiCl were mixed in a molar ratio of 5:1:2.
[0132] Comparative Example 3
[0133] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 5.55 P 0.95 Hf 0.05 S 4.75 Cl represents the composition).
[0134] Comparative Example 4
[0135] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 5.6 P 0.9 Hf 0.1 S 4.75 Cl represents the composition).
[0136] Comparative Example 5
[0137] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 5.85 P 0.9Hf 0.1 S 4.75 Cl 1.25 The composition of the representation).
[0138] Comparative Example 6
[0139] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 5.6 P 0.9 Hf 0.1 S 4.5 Cl 0.5 Br).
[0140] Comparative Example 7
[0141] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 6.1 P 0.9 Si 0.1 The composition is represented by S5Br).
[0142] Comparative Example 8
[0143] A solid electrolyte (having an argyrodite-type crystal structure and having a Li 6.2 P 0.8 Si 0.2 The composition is represented by S5Br).
[0144] For each solid electrolyte prepared in Examples 1 to 4 and Comparative Examples 3 to 8, the ionic radius (r) (unit: Å) of the cation doped at the P site is proportional to the S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ), and the ratio (c / r) of the ionic oxidation number of the cation doped at the P site to the ionic radius (r) (unit: Å) are presented in Table 1 below.
[0145] As a reference, for each solid electrolyte (not doped with cations) prepared in Comparative Examples 1 and 2, P was calculated. 5+ The ionic radius (unit: Å) value of S 2-The ratio of the ionic radius (unit: Å) of 5+ The ratio of the ionic oxidation number to the ionic radius (unit: Å) value is shown in Table 1 below.
[0146]
[0147] Experimental Example 1: X-ray diffraction analysis, particle size analysis
[0148] (Confirmation of the presence of cation doping in solid electrolytes)
[0149] The presence of cation doping of the solid electrolytes prepared in Examples 1, 4 and 5 and Comparative Examples 4 to 6 was confirmed by X-ray diffraction (XRD) analysis, and the XRD analysis was performed using a Bruker AXS D8 Endeavor XRD (voltage: 40 kV, current: 40 mA) using Cu Ka radiation (wavelength: 1.54 Å) at a scan rate of 0.02° / 0.3 sec in the 2θ range of 10° to 60°. The XRD analysis results of Examples 1, 4 and 5 and Comparative Examples 4 to 6 are shown in FIG. Figure 1 and Figure 2 middle.
[0150] Reference Figure 1 , for the solid electrolytes of Examples 1, 4, and 5, since no unreacted impurity phase was detected, it was confirmed that each of them was 100% of the argyrodite phase, and it was understood that they were doped with cations.
[0151] On the contrary, refer to Figure 2 , for the solid electrolytes of Comparative Examples 4 to 6, an excessive amount of non-reactive impurity phases were detected, estimated to be lithium halide (indicated by diamonds) and an unknown phase (indicated by inverted triangles).
[0152] (Confirmation of average particle size and span value of solid electrolyte)
[0153] The D values of the solid electrolytes prepared in Examples 1 to 5 and Comparative Examples 1 and 2 were measured using a particle size analyzer (Malvern Panalytical, Mastersizer 3000). 10 , D 50 and D 90 , and the average particle size (D 50 ) and the span values calculated according to the following formula 3 are presented in the following Table 2.
[0154] [Formula 3]
[0155] Span = [D 90 -D 10 ] / D 50
[0156]
[0157] Referring to Table 2, with respect to the solid electrolytes of Examples 1 to 5, it can be understood that they have uniform particle sizes compared with the solid electrolyte of the Comparative Example.
[0158] Experimental Example 2: Evaluation of ion conductivity retention
[0159] - Initial ionic conductivity evaluation
[0160] Immediately after preparation, 150 mg of each solid electrolyte powder prepared in Examples 1 to 4 and Comparative Examples 1 to 8 was taken out and placed in a SUS mold with a diameter of 13 mm. The voltage regulator was connected to the SUS mold in a state where the mold was mounted on a press together with PEEK for insulation. After the electrolyte structure was fully densified by pressing under a pressure of 370 MPa, AC impedance measurements were performed at a measurement frequency of 1 Hz to 7 MHz while slowly reducing the pressure and maintaining it at 100 MPa. The ionic conductivity was calculated from the measured resistance value by the Nyquist plot and is presented in Table 3 below. All measurements were performed in a drying chamber at a temperature of 22 ° C and a relative humidity of 0.7%.
[0161] - Evaluation of ionic conductivity after moisture exposure
[0162] After each solid electrolyte powder prepared in Examples 1 to 4 and Comparative Examples 1 to 8 was exposed to air with a relative humidity of 1.91% for 5 hours, 150 mg of each solid electrolyte powder was immediately taken out and placed in a SUS mold with a diameter of 13 mm. The voltage regulator was connected to the SUS mold in a state where the mold was mounted on a press together with PEEK for insulation. After the electrolyte structure was fully densified by pressing at a pressure of 370 MPa, AC impedance measurements were performed at a measurement frequency of 1 Hz to 7 MHz while slowly reducing the pressure and maintaining it at 100 MPa. The ionic conductivity after moisture exposure was calculated from the measured resistance value by the Nyquist plot and is presented in Table 3 below. All measurements were performed in a drying room at a temperature of 22 ° C and a relative humidity of 0.7%.
[0163] The ionic conductivity retention rate was calculated according to the following Formula 1 and is presented in Table 3 below.
[0164]
[0165]
[0166] Referring to Table 3, for the solid electrolytes of the embodiments, since they have better moisture stability than the solid electrolytes of the comparative examples, it can be confirmed that the ion conductivity retention rate is high even after moisture exposure. In addition, regarding the solid electrolytes of Examples 1, 2, and 4 doped with cations having a ratio (c / r) of an ion oxidation number (c) value to an ion radius (r) (unit: Å) in the range of 7.00 to 14.00, it can be confirmed that they have higher initial ion conductivity than the solid electrolyte of Example 5 doped with cations having a c / r value of less than 7.00. The reason for this is that the lower the c / r value, the higher the initial ion conductivity of the cations and S 2- However, if the c / r value is too low, P-site doping is difficult, thereby reducing the ionic conductivity performance.
[0167] Experimental Example 3: Impurity Analysis after Water Exposure
[0168] Immediately after the solid electrolyte powders in Examples 1, 2 and 5 and Comparative Examples 1 to 7 were prepared, and immediately after the solid electrolyte powders were exposed to air having a relative humidity of 1.91% for 5 hours immediately after the preparation, each powder was taken out and placed in a glass vial, and the vial was measured using a diffuse reflection accessory (8 cm -1 The NIR reflectance spectra of the solid electrolyte in the glass vial were obtained by FT-NIR spectrometer (ABB, MB3600) with 100 nm resolution and 32 scans. -1 and 4,685cm -1 After baseline calibration, the -1 Up to 4,725cm -1 The integrated values of the NIR peaks associated with Li2CO3 impurities in the range are shown in Table 4 below.
[0169] For reference, the analysis conditions are as follows.
[0170] - Coverage: 3,700 to 14,885cm -1 scope
[0171] -Interferometer mechanism: High throughput dual-pivot Michelson
[0172] -NIR source: Quartz halogen (electrically controlled)
[0173] -Laser source: solid-state laser (long life)
[0174] -Optical material: Completely non-hygroscopic lens (ZnSe)
[0175] -Detector: TE-cooled InGaAs detector
[0176] In addition, the area increase rate of the impurity peak was calculated according to the following Formula 2 and is presented in Table 4 below.
[0177]
[0178]
[0179] Referring to Table 4, compared with the solid electrolyte of the comparative example, since the area increase rate of the impurity peak of the solid electrolyte of the embodiment is low even after moisture exposure, it can be confirmed that the solid electrolyte of the embodiment has better moisture stability. In other words, it can be confirmed that the electrolyte structure of the solid electrolyte of the embodiment is maintained even after moisture exposure.
[0180] As a result, since the solid electrolyte having an argyrodite type crystal structure according to the present invention is doped with cations, the cations have an ionic radius (r) (unit: Å) value of 0.20 to 0.30 for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ), it can be understood that the decomposition and degradation of the sulfide-based solid electrolyte particles during moisture exposure can be suppressed.
Claims
1. A solid electrolyte having an argyrodite-type crystal structure doped with a cation, wherein the cation has an ionic radius (r) (unit: Å) value of 0.20 to 0.30 for S 2- The ionic radius (r s ) (unit: Å) value ratio (r / r s ).
2. The solid electrolyte according to claim 1, wherein the cation has a ratio (c / r) of an ion oxidation number (c) value to an ion radius (r) (unit: Å) value of 7.00 to 14.
00.
3. The solid electrolyte according to claim 1, wherein the solid electrolyte has a composition represented by Chemical Formula 1: [Chemical formula 1] Li a (P 1-b M b )S c X d Wherein, in Chemical Formula 1, M is at least one selected from tin (Sn), niobium (Nb), nickel (Ni), germanium (Ge), gallium (Ga), and aluminum (Al), X is at least one selected from fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and 5.0<a<7.5, 0<b≤0.7, 3.5≤c≤7 and 0.8≤d≤1.
7. 4 . The solid electrolyte according to claim 3 , wherein M is at least one selected from Sn, Nb, Ge and Al. 5 . The solid electrolyte according to claim 3 , wherein the ratio of the number of moles of M to the sum of the number of moles of P (x) and the number of moles of M (y) (y / (x+y)) satisfies 0.01 to 0.
7.
6. The solid electrolyte according to claim 1, wherein the ionic conductivity retention rate according to Formula 1 is 55% or more: in, In formula 1, The initial ionic conductivity is a value measured at 22° C. immediately after preparing the solid electrolyte, and The ionic conductivity after moisture exposure is a value measured at 22° C. immediately after the solid electrolyte is exposed to air having a relative humidity of 1.91% for 5 hours. 7 . The solid electrolyte according to claim 6 , wherein the initial ionic conductivity is in the range of 2.0 mS / cm to 20.0 mS / cm. 8 . The solid electrolyte according to claim 6 , wherein the ionic conductivity after the moisture exposure is in the range of 1.4 mS / cm to 18.0 mS / cm.
9. The solid electrolyte according to claim 1, wherein About the presence of 5,200 cm in the near infrared (NIR) spectrum -1 Up to 4,725cm -1 The impurity peak within the range of , the area increase rate of the impurity peak according to Formula 2 is in the range of 50% to 400%: In formula 2, The integrated value of the impurity peak before moisture exposure is a value obtained from the NIR spectrum measured at room temperature immediately after preparing the solid electrolyte, and The integrated value of the impurity peak after moisture exposure is a value obtained from the NIR spectrum measured at room temperature immediately after the solid electrolyte was exposed to air having a relative humidity of 1.91% for 5 hours. 10 . The solid electrolyte according to claim 9 , wherein an integrated value of the impurity peak after the moisture exposure is in the range of 1 to 20.
11. The solid electrolyte according to claim 1, wherein the average particle size (D 50 ) is in the range of 0.5μm to 4μm.
12. The solid electrolyte according to claim 1, wherein the span value ([D 90 -D 10 ] / D 50 ) is less than 4.
13. An all-solid-state battery comprising the solid electrolyte according to any one of claims 1 to 12.
Citation Information
Patent Citations
Display panels and display devices
KR1020220106849A